Faktor yang Mempengaruhi Keputusan Pembelian Online di Shopee pada Warga Desa Kuta Tengah Kabupaten Deli Serdang - Sembiring , Lidya Br; Tarigan, Eka Dewi Setia (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study aims to analyze the influence of factors affecting online purchasing decisions on Shopee among residents of Kuta Tengah Village, Deli Serdang Regency. The research uses a quantitative approach to determine the extent of influence of independent variables on dependent variables. The total population of Kuta Tengah Village is 1,310 people. The data was obtained from the Village Secretary of Kuta Tengah, and the sampling technique used the Solvin formula, resulting in 93 respondents. Data analysis was conducted using SPSS 27 with multiple linear regression analysis to determine the influence of independent variables on dependent variables. The research results indicate that Price has a positive and significant influence on Purchase Decision. This is evident from the significant value (0.000) < 0.05. Application Ease has a positive and significant influence on Purchase Decision. This is evident from the significant value (0.000) < 0.05. Transaction Security has a positive and significant influence on Purchase Decision. This is evident from the significant value (0.000) < 0.05. Simultaneously, Price (X1) and Application Ease (X2) are significantly related to Purchase Decisions.